السرقة العلمية المرتكبة خطأ أثناء إعداد البحث العلمي - زعادي محمد جلول; محجوبي زهرة (University Of Eloued جامعة الوادي, 2023)
Plagiarism is a global scourge that is not confined to the scope of a specific country, but rather that all humanity suffers from, as long as it is embodied in a behavioral deviation through which the researcher aims to appropriate the scientific effort made by others, and attribute it to himself.This totalitarian view was terribly prevalent in the university community, and this prompted some specialists to try to correct it by highlighting that scientific theft stemming from the shortcomings of the management of the university institution and the university professor himself, who by virtue of their neglect of the formation of the student inin the field of scientific honesty in particular, and in the context of scientific research methodology in general, they have created generations that have become accustomed to plagiarism without having knowledge of that. The Algerian public authorities have tried to correct this behavior, and this position by taking a series of bold steps aimed at preventing such abuses from falling into, and deterring those who begged themselves to deliberately do so by adopting ministerial resolutions 966 of 2016 and 1082 of 2016 of2020 related to the prevention and combating of scientific plagiarism
Scientific theft committed by mistake during the preparation of scientific research
مداخلة
Keywords: السرقة العلمية; التشريع الجزائري; البحث العلمي; الأستاذ الجامعي; الطالب; الجودة; Scientific plagiarism; Algerian legislation; Scientific research; University professor; Student; Quality